Elective Cesarean Delivery at Term and the Long-Term Risk for Neurological Morbidity of the Offspring - Baumfeld, Yael; Sheiner, Eyal; Wainstock, Tamar; Segal, Idit; Sergienko, Ruslan; Landau, Daniella; Walfisch, Asnat (American Journal of Perinatology, 2018)
Objective The study's objective was to determine whether mode of delivery has an impact on the long-term risk for neurologic morbidity of the offspring.Materials and Methods This population-based cohort analysis included all term singleton deliveries between 1991 and 2014. The study population was divided into two study group: elective cesarean deliveries (CD) versus vaginal deliveries (VD). Urgent cesarean deliveries, pregnancy, and delivery complications including preeclampsia and gestational diabetes were excluded. The evaluation of cumulative neurological hospitalization rate over time was performed with a Kaplan–Meier survival analysis and Cox proportional hazards models were used to study the independent association between mode of delivery and neurological morbidity while controlling for potential confounders.Results During the study period 132,054 deliveries met the inclusion criteria, 11,746 CD (8.9%), and 120,308 (91.1%) VD. A total of 3,626 neurological hospitalizations were documented with 2.70% (3,244) in the VD group as compared with 3.25% (382) in the CD group. The survival curves showed higher cumulative hospitalization rates in the CD as compared with the VD group (p ≤ 0.001). The Cox analysis demonstrated CD to be an independent risk factor for pediatric neurological hospitalizations (p < 0.001).Conclusion Term elective CD is an independent risk factor for neurological morbidity of the offspring.
Keywords: mode of delivery; neurological morbidity; autism; pervasive developmental disorder